THU0067 Is Treat-To-Target Really Working? A Longitudinal Analysis in Biodam. (15th July 2016) - Ramiro, S.; Landewé, R.; van der Heijde, D.; FitzGerald, O.; Østergaard, M.; Homik, J.; Elkayam, O.; Thorne, J.C.; Larche, M.; Ferraccioli, G.; Backhaus, M.; Boire, G.; et al.
Abstract : Background: A Treat-to-Target approach (T2T), treating patients with RA towards a target, either remission or low disease activity (T2T-REM or T2T-LDA) is nowadays recommended. However it has never been assessed whether such a strategy in daily clinical practice really leads to more patients meeting that target. Methods: BIODAM is a 2-year prospective cohort including patients in daily practice with RA from 10 countries, who were started or changed on DMARD and/or anti-TNF treatment and were followed-up every 3 months. Participating physicians were required to practice T2T per protocol. Per visit was decided whether a patient was treated according to T2T or not. T2T-REM was considered met: i) if a patient had already a disease activity score below the target (DAS28-CRP<2.6); or ii) if treatment was intensified (by increasing dosage or adding drugs) upon a DAS28≥2.6. T2T-LDA was computed using the benchmark for low disease activity (LDA) (DAS28<3.2) (T2T-LDA). The main outcome was the presence or absence of ACR/EULAR-boolean remission 3 months after T2T-REM or T2T-LDA. Another outcome analysed was sustained remission (present >6 months). The relationship between T2T and ACR/EULAR Boolean remission 3 months later (or sustained remission) was investigated using generalized estimating equations with auto-regression. Results: In total 3084 visits of 539 patients (mean (SD) age: 56 (13) years, 76% female, disease duration 6 (8) years). In 68% of the visits, T2T-REM was applied (in 79% of the visits T2T-LDA was applied). ACR/EULAR-boolean remission was reached in 15% of the visits. Appropriate application of T2T-REM led to a 50% higher likelihood of ACR/EULAR-boolean remission 3 months later than not applying T2T-REM. Both T2T-REM and T2T-LDA strategies led to lower disease activity (with an exception of DAS28 remission or DAS28-LDA). Only 9% of the treatment intensifications followed upon a DAS28 between 2.6 and 3.2, and 79% of the intensifications were applied upon a DAS>3.2. Following T2T strategies led to higher achievement of sustained remission (table ). Conclusions: A treat-to-target approach, even with a modest benchmark (DAS28 = 3.2), works and leads to a higher achievement of (sustained) ACR/EULAR-remission. Our study illustrates the importance of acting upon the data that is routinely collected in a clinical encounter. Rheumatologists should be encouraged to follow a treat-to-target approach in order to improve the outcome of their patients. Disclosure of Interest: None declared